Retour de flamme 06 : la fabuleuse enfance du cinéma - Bromberg, Serge; Hammache, Sofia; Lange, Eric; Pascaline, Peretti; Simon, Anne (Paris : Lobster Films, 2006)
- Le pêcheurs de perles / Ferdinand Zecca, 1907 (7 min) ##- Suspense / Loïs Weber, 1913 (10 min) ##- Balloonland / Ub Iwerks, 1935 (6 min) ##- Films irrévérencieux / Pathé, prod., 1905 (2 min) ##- Bip... bip... bip... ici Paris / 1950 (8 min) ##- Post no bills / Ralph Cedar, 1923 (13 min) ##- Making an american citizen / Alice Guy Blaché, 1912 (10 min) ##- Makin''em move / John Foster, 1931 (7 min) ##- Chasse à la girafe en Ouganda / Alfred Machin, 1910 (6 min) ##- The pest / Jess Robbins, 1923 (22 min) ##- Grégor et ses grégoriens / Roger Lion, 1930 (3 min) ##- Publicités (4 min) ##- Bonus : "Le raid en avion" / Willi Wolff, 1924 (21 min)
French or English language tracks with optional English or French subtitles.
film
Keywords: ACAD